AMBIENT NOISE HORIZONTAL-TO-VERTICAL SPECTRAL RATIO FOR ASSESSING SITE EFFECTS IN URBAN ENVIRONMENTS: THE CASE OF THESSALONIKI CITY ( NORTHERN GREECE ) - Panou, A. A.; Theodulidis, N.; Hatzidimitriou, P. M.; Papazachos, C. B.; Stylianidis, K. (Bulletin of the Geological Society of Greece, 2004)
250 ambient noise measurements were performed in a dense grid (about 150mX150m) covering the historical center of the city of Thessaloniki (Northern Greece), that was strongly affected by the 20/6/1978 (M=6.5) damaging earthquake. The data were processed using the method of horizontal- to-vertical (H/V) spectral ratio (Nogoshi and Igarashi, 1971; Nakamura, 1989). In order to evaluate diurnal and seasonal variation (summer - winter) of the ambient noise H/V spectral ratio, systematic measurements were performed in eight sites. The fundamental frequency (fo) and the corresponding H/V amplitude level (Ao) from the ambient noise H/V spectral ratio for each site were calculated. Spatial interpolation of the fundamental frequency (fo) and the corresponding H/V amplitude level (Ao) was attempted between all points and respective contour maps were produced. Diurnal variation of the ambient noise H/V spectral ratio showed that it is preferable to perform measurements during the calm hours of a day, when manmade noise is relatively low. However, no systematic seasonal fluctuation effect on the ambient noise H/V spectral ratio was identified for the city of Thessaloniki. Contour maps of both fundamental frequency (fo) and corresponding H/V amplitude level (Ao) were compared versus the macroseismic data of the 1978 earthquake (Leventakis, 2003), as well as with related geological (IGME, 1978) and geotechnical (Anastasiadis et al., 2001) studies for the same area. Damage distribution due to 20/6/1978 earthquake (Penelis et al., 1985) was also converted to EMS_98 (European Macroseismic Scale, 1998). For seventy buildings, made of reinforced concrete, we have also compared the obtained results with the dynamic amplification of the buildings (Ubuilding) at the fundamental soil frequency (fo). The results encourage the use of ambient noise measurements along with the (H/V) spectral ratio technique as a nonexpensive and fast tool in microzonation studies to be carried out in urban environments.